Investigating the Effect of Exploration Game within a Contextual Learning Setting on Pupils’ Vocabulary Mastery - Zega, Multi Krisna; Zamago, Dirman Yanto; Gulo, Hubertus Kristofan; Mendrofa, Kelvin Rahmana Jaya; Zebua, Percis; Telaumbanua, Yasminar Amaerita (DIKSI: Jurnal Kajian Pendidikan dan Sosial, 2025)
Vocabulary mastery is a crucial aspect of English learning in elementary schools, but classroom teaching often relies heavily on mechanical memorization methods that do not provide meaningful context. These methods typically do not keep students interested or help them retain vocabulary over time. This study explores the effectiveness of using exploration games within the Contextual Teaching and Learning framework to improve vocabulary mastery among fifth grade students. The need for this research comes from the desire to develop learning methods that actively involve students and link vocabulary learning to real-life situations. The study aimed to determine if exploration game-based contextual learning significantly improves students' vocabulary mastery. The research used a quantitative approach with a one-group pretest-posttest quasi-experimental design. The participants were 18 fifth grade students from an elementary school, chosen through total sampling. Data were gathered using vocabulary tests given before and after three sessions of exploration game-based instruction. The data were analyzed using descriptive analysis and the Wilcoxon Signed Rank test. The results showed a significant improvement in vocabulary mastery for all participants, with notable score increases following the intervention. Statistical analysis confirmed that the improvement was significant and had a large practical impact. In conclusion, integrating exploration games with Contextual Teaching and Learning is effective in enhancing vocabulary mastery for elementary students and presents a meaningful alternative to traditional vocabulary teaching methods.